Effects of farm origin and respiratory disease on pig performance - Turlington, W.H.; Maxson, P.F.; Allee, G.L.; Potter, S.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Slaughter checks were conducted on 392 pigs from 9 producers to evaluate factors affecting pig performance, based on the age of the pig and its health status. Among herds, weight per day of age ranged from 1.07 to 1.32 lb/day, whereas days to 230 lb varied from 172 to 214 days. Based on statistical analysis, differences among farms accounted for 40% of the total variation in pig performance, whereas respiratory disease accounted for 20%. From our data, it was concluded that management is the major factor controlling pig performance, yet the health status of the animal is also a contributing factor.
Keywords: Swine; Farm origin; Respiratory disease; Performance